PREVALENCE OF DIABETIC RETINOPATHY AMONG INDIVIDUALS SCREENED POSITIVE FOR DIABETES IN FIVE COMMUNITY-BASED EYE CAMPS IN NORTHERN KARACHI, PAKISTAN - Din, Jamal -u-; Qureshi, Mohammad Babar; Khan, Akhtar Jamal; Khan, Mohammad Daud; Ahmad, Khabir (Journal of Ayub Medical College Abbottabad, 2006)
Background: Population-based data on the prevalence of diabetic retinopathy in Pakistan are lacking. We determined the prevalence of diabetic retinopathy among individuals screened positive for diabetes in five community-based eye camps in northern Karachi, Pakistan. Methods: In summer 2002, five community-based eye camps were set up in Karachi, Pakistan’s largest city. All individuals aged 30 years or older who visited the camps were requested to participate in the study. Those who agreed were screened for diabetes and those found to have the disease were referred to an eye hospital for diabetic retinopathy screening. Verbal informed consent was obtained from all participants at the examination site. Our main outcome measure was diabetic retinopathy, which was classified as non-proliferative diabetic retinopathy (NPDR), severe NPDR, and proliferative diabetic retinopathy (PDR). Our grading was based on clinical examination. Results: A total of 912 subjects were screened for diabetes mellitus. Of these, 160(17.5%) had diabetes- 1.8% had type I diabetes and 15.9% had type II diabetes. One hundred and eight individuals visited the hospital for ophthalmic examination. Of them, 15.7% had diabetic retinopathy. The prevalence of diabetic retinopathy was higher among individuals with type I diabetes, with greater duration of diabetes, and among women. The commonest form of diabetic retinopathy was non-proliferative (76.5% [mild: 35.3 %, moderate: 29.4 %, and severe: 11.8 %]), followed by maculopathy (17.6 %) and proliferative diabetic retinopathy (5.9 %). Conclusion: More systematic and population-based research is needed to estimate the prevalence of and identify risk factors for diabetic retinopathy in Pakistan. Key words: diabetic retinopathy, prevalence, Karachi, Pakistan